Outcomes of cochlear implantation among prelingual children with different age at implantation - Siti Hufaidah Konting
Cochlear Implant (CI) is an implanted electronic device designed to produce useful hearing sensations to a person with severe to profound sensorineural hearing loss (SNHL). Early implantation is recommended for prelingual children that receive minimal benefits from the super-power hearing aid. Late of cochlear implantation among prelingual children is often associated with poor outcome and prognosis post-operation due to brain plasticity. Thus, the aims of this study were to compare CI outcome among pre-lingual children with different ages at implantation, and to investigate the correlation of relevant intrinsic and extrinsic factors to the CI outcome. A total of 30 pre-lingual recipients of CI from the University Malaya Medical Centre (UMMC) were divided into two groups, based on their age at implantations; i) early implantation (≤4 years old, n=12) and ii) late implantation (> 4 years old, n=18).The study participants were implanted with MED-EL (n=29) and Oticon Medical (n=1) CIs. The ages at implantation for the early group were between 1.4 and 4 years old (mean 3.2, SD 0.8), and for the late group the ages were between 4.3 and 14.7 years old (mean 6.8, SD 2.9). Five tests were used to evaluate the outcome measures: i) aided thresholds ii) Meaningful Auditory Integration Scale (MAIS), iii) Meaningful Use of Speech Scale (MUSS), iv) Speech Tests, and v) CAEP test. The outcomes of the early and late implanted groups were statistically compared. The results showed improved auditory detection and higher scores from parental questionnaires post-implantation in both groups. The early implanted group was found to have better outcomes in terms of audiological assessments and shorter CAEP P1 latency compared to the late implanted group. However similar improvement gains in parental self-report questionnaires were found in both groups. The intrinsic factors that affecting the CI outcomes were the age of subjects, the duration of implantation and the age at implantation. Whereas the extrinsic factors were the maternal educational and occupational level. In conclusion, both early and late implantations resulted in improved audiological assessments and parental self-report scores post-implantation, with the early implanted group showing rapid brain maturation than the late implanted group. This study recommends early implantation to be prioritised, as it provides better outcome. However, if it is not feasible to implant early, consideration with realistic expectation should be given to implant slightly older children, as they also derive benefits from the CI as observed in this thesis.